2009
DOI: 10.1002/adfm.200801125
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Improved Efficiency of InGaN Light‐Emitting Diode With Bottom Photonic Crystal Fabricated by Anodized Aluminum Oxidxe

Abstract: The improved performance of a bottom photonic crystal (PC) light‐emitting diode (LED) is analyzed based on internal quantum efficiency (ηint) and light‐extraction efficiency (ηex). The bottom PC is fabricated by anodized aluminum oxide nanopatterns and InGaN quantum wells (QWs) are grown over it. Transmission electron microscopy images reveal that threading dislocations are blocked at the nanometer‐sized air holes, resulting in improved optical emission efficiency of the QWs. From temperature‐dependent photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…3(a). The temperature-dependent PL intensity can be well fitted using the following Arrhenius formula3243444546: where I(T) represents the normalized integrated PL intensity. The parameters C 1 and C 2 are two constants related to the density of non-radiative recombination centres in the samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3(a). The temperature-dependent PL intensity can be well fitted using the following Arrhenius formula3243444546: where I(T) represents the normalized integrated PL intensity. The parameters C 1 and C 2 are two constants related to the density of non-radiative recombination centres in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Based on photoluminescence spectra measured at different temperatures, a systematic and mature theory has been developed to study the defects related to non-radiative processes3233, localized states2034, and carrier transport dynamics203536. A series of physical equations are widely used to characterise and fit the above physical processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al used Zn and Mg for ion implantation at the GZO thin layer and then adopted rapid thermal annealing to enhance the LEE of short-wavelength purple and ultraviolet LEDs by 1.4–2.5 times that of a traditional LED [14]. Ryu et al adopted anodic aluminum oxide (AAO) to produce a photonic crystal structure at the n-GaN layer of LEDs, and transmission electron microscopy (TEM) images showed that screw dislocations in the LED structure were blocked, thus enhancing the general luminous efficiency by approximately 23% [15]. Cates et al adopted laser etching to produce a repeated microstructure on the emitting surface of a yttrium aluminum perovskite scintillation crystal activated by cerium (formula YAlO 3 :Ce, abbreviated as YAP:Ce) and reduced the total reflection of light via surface roughening.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts, including surface roughening [7,8], the formation of photonic crystals [9,10], the use of patterned sapphire substrates (PSS) [11,12], and the use of an air-gap structure inside the LED [13], were made to suppress the TIR.…”
Section: Introductionmentioning
confidence: 99%